Volume Staged Radiosurgery for Large Arteriovenous malformation - A case study - Tuong, Pham Nguyen; Khoa, Tran; Hiep, Pham Nhu; Thanh, Nguyen Van; Bao, Dang Hoai (Tạp chí Y học lâm sàng Bệnh viện Trung Ương Huế, 2025)
Introduction: Large Arteriovenous malformations (AVMs) are challenges in management because of outcomes and adverse effects. Volume Staged Radiosurgery has been an appropriate approach when removal resection and embolization are not recommended. Case presentation: A 53 year-old gentleman was diagnosed with a large intracranial AVM with persistent headache and short-term seizure. Brain MR and angiograph showed a bulky volume of AVM nidus. Removal resection and embolization were not recommended because of high risk of adverse effects. Patient was treated by volume staged radiosurgery. Management and outcome: Radiosurgery was divided into two stages. First stage was 15 Gy to the anterior half, and second one was 13 Gy to the posterior half of whole AVM, interval time was 5 months. 5 months post-treatment, there was still remained shunts for right internal carotid artery (ICA), completely obliteration for right external carotid artery (ECA). One year post-treatment, obliteration for right ICA was completed. Discusion: Volume Staged Radiosurgery is a potential treatment option for large AVM with controlled and obliteration efficacy, especially to AVMs which are not appropriate for removal surgery and embolization.